A 12-year analysis of pacing strategies in 200- and 400-m individual medley in international swimming competitions - Saavedra, J. M.; Escalante, Y.; Garcia-Hermoso, A.; Arellano, R.; Navarro, F. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to ascertain the pacing strategies employed in 200- and 400-m individual medley events and which style was the most determinant for the final performance as a function of sex and classification in international competitions. Twenty-six international competitions covering a 12-year period (2000-2011) were analyzed retrospectively: Olympic Games, World Championships, European Championships, Commonwealth Games, Pan Pacific Games, U.S. Olympic Team Trials, and Australian Olympic Trials. The data corresponded to a total of 1,643 swimmers' competition histories (821 men, 822 women). A 2-way analysis of variance (sex [2 levels: men, women] × classification [3 levels: 1st to 3rd, 4th to 8th, 9th to 16th]) was performed for each stroke (butterfly, backstroke, breaststroke, and freestyle). The Bonferroni post hoc test was used to compare means. Pearson's simple correlation coefficient was used to determine correlations between the style (sections time) and the final performance (total time). The men employed a smaller percentage of their event times in the breaststroke than did the women and a greater percentage in the freestyle in both the 200- and 400-m distances, with the fastest style for both sexes being the butterfly. Considering only the medalists, in men (200 and 400 m), the backstroke was the style that most determined their final performance, whereas in women, it was the backstroke (200 m) or freestyle (400 m). It was concluded that in general the men apply a positive pacing strategy in the 200- and 400-m individual medley events, whereas the women apply a negative pacing strategy. The practical application of the study is that it suggests the need for a differentiated approach in training men and women individual medley swimmers.